1991
DOI: 10.1111/j.1570-7458.1991.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and diet on oviposition rate and development time of the New Zealand flower thrips, Thrips obscuratus

Abstract: The life history of New Zealand flower thrips (Thrips obscuratus (Crawford), Thysanoptera: Thripidae) was studied using a simple laboratory rearing method. The effects of temperature and diet on oviposition rate and development time were examined. Oviposition rate increased with increasing temperature between 10°C and 25°C. Development time for individual instars and for total development decreased with increasing temperature between 10°C and 27°C. Total development time ranged from 50 days at 10°C (female) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 17 publications
3
46
1
2
Order By: Relevance
“…The third group acknowledges that alternative food causes a more numerous offspring and a shorter life cycle (Teulon and Penman 1991), but it most often diminishes the predatory effectiveness of the insect (van Rijn and Sabelis 1993). The host plants do not only provide for alternative food but also for a shelter against potential attackers; besides it was established that the plants signalize to the predators the presence of their potential prey (Price et al 1980;Dicke 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The third group acknowledges that alternative food causes a more numerous offspring and a shorter life cycle (Teulon and Penman 1991), but it most often diminishes the predatory effectiveness of the insect (van Rijn and Sabelis 1993). The host plants do not only provide for alternative food but also for a shelter against potential attackers; besides it was established that the plants signalize to the predators the presence of their potential prey (Price et al 1980;Dicke 1994).…”
Section: Resultsmentioning
confidence: 99%
“…En este momento las poblaciones se incrementan rápidamente, presumiblemente debido a la alta calidad nutricional de las flores y los tejidos en crecimiento. Se sabe que el polen reduce el tiempo de desarrollo y aumenta la supervivencia y la fecundidad de las hembras de P. kellyanus (Blank y Gill, 1997;Baker et al, 2002;Varikou et al, 2010), también se ha citado para otras especies de trips que las larvas privadas de polen presentan un menor desarrollo y una mayor mortalidad (Murai y Ishii, 1982;Teulon y Penman, 1991). Durante la caída de pétalos y debido a que esto ocurre en un lapso de tiempo muy corto, muchas de estas larvas caen al suelo, otras se mueven por el árbol buscando otras flores (observaciones propias al capturar muchas larvas en trampas pegajosas blancas en este periodo) y otras se quedan alimentándose en la zona mas protegida y más tierna que les queda, la unión del ovario con el disco floral.…”
Section: Discusión Generalunclassified
“…The abundance of KCT populations in citrus orchards was strongly related with the spring flowering, as was previously observed by , and . Like other thrips species, KCT requires pollen for its reproduction and larval growth (Kirk, 1984;Teulon and Penman, 1991;Baker et al, 2002). Citrus flowers provide a good source of pollen, and moreover, adequate breeding sites for KCT.…”
mentioning
confidence: 99%
“…A similar pattern was also observed for Frankliniella tritici (Fitch), it was more abundant on cotton flowers than on seedling cotton in northern Florida (Osekre et al, 2009). Teulon and Penman, (1991) found that pollen and nectar are important food sources for thrips development and reproduction and hence this could explain the high abundance of both F. occidentalis and F.…”
Section: Thrips Abundance and Diversity On Cotton And Other Cropsmentioning
confidence: 99%
“…This implies that unlike T. tabaci the seasonal abundance of F. occidentalis on cotton was primarily driven by cotton flowers. Teulon & Penman, (1991) found that pollen to be an important source of food for thrips development and reproduction and this could explain the high abundance of F.…”
mentioning
confidence: 99%